Reading Identity, Reading Essence: A Strategic Essentialist Approach to Mulk Raj Anand’s Untouchable - Ilhaam, Saleha (South Asian Journal of Social Sciences and Humanities, 2021)
The term strategic essentialism, coined by Spivak, is generally understood as "a political strategy whereby differences (within Group) are temporarily downplayed, and unity assumed for the sake of achieving political goals." On the other hand, essentialism focuses that everything in this world has an intrinsic and immutable essence of its own. The adaption of a particular “nature” of one group of people by way of sexism, culturalization, and ethnification is strongly linked to the idea of essentialism. Mulk Raj Anand’s Bakha is dictated as an outcast by the institutionalized hierarchy of caste practice. He is essentialized as an untouchable by attributing to him the characteristic of dirt and filth. However, unlike other untouchables, Bakha can apprehend the difference between the cultured and uncultured, dirt and cleanliness. Via an analysis of Anand’s "Untouchable," the present article aims to bring to the forefront the horrid destruction of the individual self that stems from misrepresentations of personality. Through strategic essentialism, it unravels Bakha’s contrasting nature as opposed to his pariah class, defied by his remarkable inner character and etiquette. The term condemns the essentialist categories of human existence. It has been applied to decontextualize and deconstruct the inaccurately essentialized identity of Bakha, which has made him a part of the group he does not actually belong to.